In-Depth Exploration of The Constraints Connected to Diverse Curriculum Designs on A Global Scale: A Literature Review - Shaoan, Md Mirajur Rhaman; Phan, Thi Anh Tu; Okafor, Miracle Uzochukwu; Lahinta, Ayu Novianti; Namayakkara, Punsadini Upamalika (Future Science / FSH-PH Publications, 2025)
This literature review thoroughly examines the challenges asso-ciated with diverse curriculum designs across various educational contexts worldwide. The study identifies key constraints and elabo-rates on how design-based curricula effectively implement diverse educational approaches. The global challenges of diverse curriculum designs arise from sociocultural disparities, fragmented policies, and unequal distribution of resources. Research indicates that rigid national standards often conflict with local educational needs, limit-ing inclusivity and adaptability. Additionally, the review explores how these challenges impact educational outcomes and curricula, highlighting those global benchmarks may marginalize indigenous knowledge systems and overlook the unique needs of refugee stu-dents. The findings emphasize the necessity for adaptive strategies and context-sensitive approaches to address these challenges and promote inclusive educational practices. Curriculum design should balance global competencies with local relevance. This review con-tributes to the broader discussion on global education reform by providing insights for policymakers, educators, and researchers who aim to enhance curricular diversity and tackle the barriers that hinder effective integration. Addressing these challenges is essential for fostering equitable education, promoting cultural preservation, and preparing students for an interconnected world.